ATMOSFEAR: Horror of nature and the nature of horror in Algernon Blackwood - Angeloch, Dominic (Orbis litterarum, 2025)
The impact that the stories of Algernon Blackwood (1869–1951) have had on the literature of the uncanny can hardly be overestimated. However, there is almost no research on Blackwood's life and work. Against the background of a presentation of themes and motifs of Blackwood's narrative œuvre, this article develops a characteristic of his poetics. It consists in first calling up conventions of narrative, which are also conventions of thought, and conventions of thought, which are also conventions of narrative, and then reversing them from within. This is shown in detail in The Willows (1907)—a story that has decisively shaped the entire tradition of uncanny tales because it solves the tasks of the poetics of the “strange” or “weird” uncanny in an exemplary manner. Yet this is also precisely what makes it so difficult to grasp what is actually going on in it, what it is actually telling us about and, above all, how. The events narrated are uncanny, even disturbing—but how can that be when there is no discernible actual event and the perceived threat remains absolutely intangible throughout the story? A precise narrative analysis shows that what was suspense in traditional ghost or horror genre tales becomes atmosphere here, and what was uncanny becomes thinking in as well as of fear.